2017
DOI: 10.1111/hex.12585
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities about stoma‐related quality of life from the perspective of people with a stoma: A pilot survey

Abstract: BackgroundThere is a recognized need to include patients in setting research priorities. Research priorities identified by people with a stoma are rarely elicited.ObjectivesTo improve the quality of life of people with a stoma through use of evidence‐based practice based on research priorities set by patients.Design and MethodsOnline pilot survey publicized in 2016 via United Kingdom stoma charities. People ranked nine stoma‐related quality of life topics in order of research priority.ParticipantsPeople 16 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…These included the Ostomy Life Study reported by Claessens et al . which comprised over 4000 patients with stomas from 11 countries and a UK‐based survey of research topics of importance to 225 stoma patients . Although these studies were taken into account during the design of the stoma‐specific score, the majority reflect only quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included the Ostomy Life Study reported by Claessens et al . which comprised over 4000 patients with stomas from 11 countries and a UK‐based survey of research topics of importance to 225 stoma patients . Although these studies were taken into account during the design of the stoma‐specific score, the majority reflect only quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…Other sources used included literature and systematic reviews of stomas and complications [17,18], current Google trends analyses of the recorded searches on the topics related to stoma care and large patient surveybased studies. These included the Ostomy Life Study reported by Claessens et al which comprised over 4000 patients with stomas from 11 countries and a UK-based survey of research topics of importance to 225 stoma patients [19,20]. Although these studies were taken into account during the design of the stoma-specific score, the majority reflect only quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…The third domain encompasses diseases where nursing research is scarce, and as a result, more research is urgently called for. Stroke (Lightbody, 2017;Rowat et al, 2016), heart failure (Stamp et al, 2018), Parkinson's disease (Shin & Habermann, 2016), osteoarthritis (Robbins & Kulesa, 2012), diabetes (Graue et al, 2013;Iversen et al, 2016) and stoma (Hubbard et al, 2017) are considered to be the above-mentioned areas of diseases. With respect to nursing research on diabetes, Iversen et al (2016) believe that future research may benefit from larger nurse-led research programmes organized into networks to share knowledge and expertise across national groups.…”
Section: Diseases and Specific Fields From The Nursing Perspectivementioning
confidence: 99%
“…Interventions are needed that have the potential to improve the QoL for this group of patients. Physical activity (PA) has been identified by patients with a stoma as a research priority in relation to their QoL [20]. No studies have been conducted about associations between PA and patient-reported outcomes in people with a stoma.…”
Section: Introductionmentioning
confidence: 99%